Assessing the Open Unemployment Rate in Bali: Evidence from Regional Panel Data in Bali - Adzim, Fauzul; Prajanti, Sucihatiningsih Dian Wisika (Journal of Economic Education, 2021)
This study aims to analyze the effect of foreign investment, domestic investment, economic growth, wages, population, and education on the level of open unemployment in the Province of Bali. This research is a quantitative study using panel data during the period 2014 - 2018 with observations of nine regencies / cities in Bali Province. The analytical method used panel data regression. Based on the model selection test with the Lagrange multiplier, the result is obtained that the random effect model is the right model to use in this study. The results of hypothesis testing using the t test indicate that foreign investment variable partially has a negative but insignificant effect on the level of open unemployment with a coefficient of -0.000702. The domestic investment variable has a negative but insignificant effect on the level of open unemployment with a coefficient of -0.013545. The economic growth variable has a negative and significant effect on the level of open unemployment with a coefficient of -2.726141. The wage variable has a negative and significant effect on the level of open unemployment with a coefficient of -2.156453. The population variable has a positive and significant effect on the level of open unemployment with a coefficient of 0.157335. The education variable has a positive and significant effect on the level of open unemployment with a coefficient of 3.465220